Progressive Familial Intrahepatic Cholestasis in Korea: A Clinicopathological Study of Five Patients - Hyo Jeong Kang; Soon Auck Hong; Seak Hee Oh; Kyung Mo Kim; Han-Wook Yoo; Gu-Hwan Kim; Eunsil Yu (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background Progressive familial intrahepatic cholestasis (PFIC) is a heterogeneous group of autosomal recessive liver diseases that present as neonatal cholestasis. Little is known of this disease in Korea. Methods The records of five patients histologically diagnosed with PFIC, one with PFIC1 and four with PFIC2, by liver biopsy or transplant were reviewed, and ATP8B1 and ABCB11 mutation status was analyzed by direct DNA sequencing. Clinicopathological characteristics were correlated with genetic mutations. Results The first symptom in all patients was jaundice. Histologically, lobular cholestasis with bile plugs was the main finding in all patients, whereas diffuse or periportal cholestasis was identified only in patients with PFIC2. Giant cells and ballooning of hepatocytes were observed in three and three patients with PFIC2, respectively, but not in the patient with PFIC1. Immunostaining showed total loss of bile salt export pump in two patients with PFIC2 and focal loss in two. Lobular and portal based fibrosis were more advanced in PFIC2 than in PFIC1. ATP8B1 and ABCB11 mutations were identified in one PFIC1 and two PFIC2 patients, respectively. One PFIC1 and three PFIC2 patients underwent liver transplantation (LT). At age 7 months, one PFIC2 patient was diagnosed with concurrent hepatocellular carcinoma and infantile hemangioma in an explanted liver. The patient with PFIC1 developed steatohepatitis after LT. One patient showed recurrence of PFIC2 after 10 years and underwent LT. Conclusions PFIC is not rare in patients with neonatal cholestasis of unknown origin. Proper clinicopathologic correlation and genetic testing can enable early detection and management.